2016
DOI: 10.4338/aci-2015-10-ra-0130
|View full text |Cite
|
Sign up to set email alerts
|

Patient Experiences Using an Inpatient Personal Health Record

Abstract: SummaryObjective: To investigate patients' experience using an inpatient personal health record (PHR) on a tablet computer to increase engagement in their hospital care. Methods: We performed observations and conducted semi-structured interviews with 14 post-operative cardiac surgical patients and their family members who received an inpatient PHR. Themes were identified using an inductive coding scheme. Results: All participants responded favorably to having access to view their clinical information. A majori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 63 publications
1
57
0
3
Order By: Relevance
“…Prior research has shown inconsistent conclusions regarding associations between portal use and patient satisfaction; with wide variability in the offered portal features, the outcomes evaluated, and the populations studied [ 4 , 10 , 14 , 31 ]. In addition, the potential of patient portals for patients with chronic conditions is documented, but relatively nascent for cancer [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has shown inconsistent conclusions regarding associations between portal use and patient satisfaction; with wide variability in the offered portal features, the outcomes evaluated, and the populations studied [ 4 , 10 , 14 , 31 ]. In addition, the potential of patient portals for patients with chronic conditions is documented, but relatively nascent for cancer [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, assessments of patient portal use among hospitalized cancer patients are limited [ 8 , 26 30 ]. For many patients, the hospital is a challenging and intimidating setting, compounded by unmet information needs and limited patient engagement [ 24 , 31 ]. The rapid dynamic and pace of clinical care, changing medical teams, reliance on verbal communication, and absence of an established relationship with the care providers further challenge patients’ effective participation in their own care [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…the less favorable responses towards features like sharing notes with clinicians that promoted active engagement in [58]). Our findings reaffirm that patients need better tools to support them in collaboratively tracking their health while in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, information on whiteboards is often not up to date [26,49] and only shows information that clinicians think patients ought to know, rather than information sought by patients themselves [26]. Compounding the problem, online information sources like patient portals that are frequently available outside the hospital are not always available in hospitals [20,25], even though patients find them valuable [25,41,58]. …”
Section: Related Workmentioning
confidence: 99%
“…The lack of quality studies and the heterogeneous nature of conditions supported by eHealth prevent full unequivocal endorsement of the cost-effectiveness of technology-driven approaches [ 10 , 11 ]. The expedient delivery and low-cost development afforded by Web 2.0 apps may facilitate further access to eHealth [ 12 ] and wider health information technology [ 13 ], including patient-reported health records [ 14 ]. The Web 2.0 platform has increased participation through social media and the sharing of experience due to the ease of posting materials such as video files and online forums [ 15 ].…”
Section: Introductionmentioning
confidence: 99%